Testing models of post‐traumatic intrusions, trauma‐related beliefs, hallucinations, and delusions in a first episode psychosis sample. (13th November 2018) - Peach, Natalie; Alvarez‐Jimenez, Mario; Cropper, Simon J.; Sun, Pamela; Bendall, Sarah
Abstract : Objective: There is increasing evidence that childhood trauma may play a role in the aetiology of psychosis. Cognitive models implicate trauma‐related symptoms, specifically post‐traumatic intrusions and trauma‐related beliefs as primary mechanisms, but these models have not been extensively tested. This study investigated relationships between childhood trauma, psychotic symptoms (hallucinations and delusions), post‐traumatic intrusions, and trauma‐related beliefs while accounting for comorbid symptoms. Methods: Sixty‐six people with first episode psychosis aged between 15 and 24 years were assessed for hallucinations, delusions, childhood trauma, post‐traumatic intrusions, post‐traumatic avoidance, and trauma‐related beliefs. Results: Fifty‐three per cent of the sample had experienced childhood trauma, and 27% met diagnostic criteria for post‐traumatic stress disorder. Both post‐traumatic intrusions and trauma‐related beliefs mediated the relationships between childhood trauma and hallucinations, and childhood trauma and delusions. Multiple regression analyses revealed that post‐traumatic intrusions (but not childhood trauma, post‐traumatic avoidance, or trauma‐related beliefs) were independently associated with hallucination severity (β = .53, p = .01). Post‐traumatic intrusions and trauma‐related beliefs (but not childhood trauma or post‐traumatic avoidance) were independently associated with delusion severity (β = .67, p < .01 and β = .34, p < .01, respectively). Conclusions: These findings support cognitive models that implicate post‐traumatic intrusions in hallucination aetiology, and post‐traumatic intrusions and trauma‐related beliefs in delusion aetiology. The results suggest that trauma and post‐traumatic stress disorder, including trauma‐related beliefs, should be addressed in the assessment and treatment of people with early psychosis. Practitioner points: Trauma and post‐traumatic stress disorder, including trauma‐related beliefs, should be addressed in the assessment and treatment of people with early psychosis. Routine assessment of childhood trauma and PTSD in clinical services dealing with young people with first episode psychosis is needed. These findings support cognitive models of trauma and hallucinations and delusions.